2009
DOI: 10.2146/ajhp080255
|View full text |Cite
|
Sign up to set email alerts
|

Stability of fentanyl 5 μg/mL diluted with 0.9% sodium chloride injection and stored in polypropylene syringes

Abstract: Fentanyl 5 microg (as the citrate) per milliliter in 0.9% sodium chloride injection, packaged in polypropylene syringes and stored protected from light, was stable for at least 90 days in controlled ambient conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 2 publications
0
11
0
2
Order By: Relevance
“…Some important formulation considerations for clinical usage are drug concentration [28], ease of administration [29], and formulation stability during storage [30, 31]. Many formulations made from liposomes or polymer-based systems exist as colloidal liquids, which are generally stable for short periods of time [32].…”
Section: Introductionmentioning
confidence: 99%
“…Some important formulation considerations for clinical usage are drug concentration [28], ease of administration [29], and formulation stability during storage [30, 31]. Many formulations made from liposomes or polymer-based systems exist as colloidal liquids, which are generally stable for short periods of time [32].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that fentanyl sterile solution packaged in medical and hospital devices, such as polypropylene syringes, polyvinylchloride bags and patient-controlled delivery systems requires especial precautions for maintaining drug stability, depending on the packaging material, temperature, storage life and duration of drug administration (DONNELLY, 2005; CHAPALAIN-PARGADE et al, 2006;MCCLUSKEY et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Entretanto, outros fatores devem ser averiguados, como as condições pontuais de armazenamento e uso. Alguns estudos demonstram que soluções de fentanila acondicionadas em seringas, bolsas e sistemas de analgesia controlada pelo paciente requerem precauções especiais a fim de manter a estabilidade do fármaco (11)(12)(13).…”
Section: Figura 2 -Curva De Calibração Do Citrato De Fentanilaunclassified